2014
DOI: 10.17221/7244-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between cytokine profile,antibody titre and viral load during sub-clinical chicken anaemia virus infection

Abstract: Th e present work was carried out to investigate the correlation between viral load and the cytokine profi le and virus specifi c antibody levels at fi ve day intervals up to 25 days post infection (dpi) in various tissues of chicks infected with chicken infectious anaemia virus (CIAV) at six weeks of age (sub-clinical infection). For determining the viral load in the various tissues, recombinant plasmid VP2-pET32b was prepared and serially diluted tenfold for the generation of a standard curve using real time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 49 publications
2
13
0
Order By: Relevance
“…It was found that the virus concentration in the tissues of positive control birds (group E) was higher than that of herbal treatment groups, with an increase in viral load from 7th to 14th DPI. This pattern of virus Immunomodulatory and prophylactic efficacy of herbal extracts against experimentally induced… 117 multiplication correlates with the observations from other studies in which the virus was inoculated at clinically susceptible age [14,15]. All the four herbal treated groups showed better response against CIAV infection as evidenced by the viral load measurements by qPCR and CMI responses.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…It was found that the virus concentration in the tissues of positive control birds (group E) was higher than that of herbal treatment groups, with an increase in viral load from 7th to 14th DPI. This pattern of virus Immunomodulatory and prophylactic efficacy of herbal extracts against experimentally induced… 117 multiplication correlates with the observations from other studies in which the virus was inoculated at clinically susceptible age [14,15]. All the four herbal treated groups showed better response against CIAV infection as evidenced by the viral load measurements by qPCR and CMI responses.…”
supporting
confidence: 87%
“…For the quantification of CIAV genome (DNA) in various tissues, isolated DNA samples were used for qRT-PCR analysis in a MX 3000P thermal cycler (Stratagene, California, USA). The forward and reverse primers used for qRT-PCR were VP2F (5 0 -ATGGCAA-GACGAGCTCGC-3 0 ) and VP2R (5 0 -TCACACTATACG TACCGGGG-3 0 ), respectively, that provided an amplicon of 178 bp size [15]. Duplicate sets of each reaction sample were prepared using 10 ll of QuantiFast SYBR Green PCR master mix (Qiagen, Hilden, Germany), 2.5 pmol each of forward and reverse primers, 2 ll of diluted DNA samples and nuclease-free water to make final reaction volume of 20 ll.…”
mentioning
confidence: 99%
“…In outbreaks of coccidiosis, IBD and bursal atrophy are associated with an increase in lesion severity and mortality and apparent failure of anticoccidial drug treatments (Hoerr, 2010;Kegne and Chanie, 2014). Chicken anaemia virus (CAV, Circoviridae) is vertically transmitted from hens suffering from acute infections during egg production, and is transmitted to the developing embryo (Wani et al, 2014). When the chick hatches, CAV targets haemocytoblasts in the bone marrow and lymphocytes in the thymus, resulting in aplastic anaemia, thrombocytopenia, leukopenia, and thymus depletion in chickens from seven to 14 days of age (Dhama et al, 2008;Umar et al, 2014).…”
Section: Agentmentioning
confidence: 99%
“…Chicken infectious anaemia is now largely controlled by ensuring that hens are exposed to CAV prior to the onset of lay. The hen develops antibody to CAV that is transferred to and protects chicks, even though the hen may continue to shed CAV through the reproductive tract (Wani et al, 2014). As a result of broad application of this basic control, blue wing disease is observed less frequently in broiler and layer production today.…”
Section: Agentmentioning
confidence: 99%
See 1 more Smart Citation